PENGARUH BIAYA OPERASI TERHADAP PROFITABILITAS PADA PT. PLN (PERSERO) BANDUNG - Yusuf Tanjung; Hendra Abu Bakar (JURISMA : Jurnal Riset Bisnis & Manajemen, 2013)
Operating cost is very important in company especially in its operational activities. It is expected that sales of existing results, we can extract the optimal profits for the company in accordance with the desired target. and the operating costs are expected to have optimal profit so that company profitability reached.  The sole purpose of this paper are: To determine Operating Cost and to know the profitability of the Sub. Directorate KC / CKB PT. PLN  (PERSERO) BANDUNG Indonesia (Persero) Bandung.The method used in this research is descriptive method such as observation, interview and filed test with quantitative approach. While the data analysis using statistic method to know the influence of operating cost to profitability, and descriptive quantitative analyze method for knowing operational cost development and to measures the profitability using correlation between weight cost with sales that was known as operating ratio, the "t" test in processed data by using SPSS 16.0 for Windows.Based on this research shows that there is influence between operational cost on profitability. Level of relation (correlation) is very closely two variables, that is r = - 0.800 with a negative correlation value. The point is that if the greater operating costs, the lower profitability or conversely the lower the operating costs, the greater the profitability of the company. Level of influence that happened is at 36% and the balance of 34% influenced by other factors. So we can conclude that there are operation costs affect the profitability of the Sub. Directorate KC / CKB PT. PLN  (PERSERO) BANDUNG (Persero) Bandung.  Keywords: Operating Cost, Profitability